Clima Organizacional y Seguridad Laboral en la Ladrillera Merkagres (2022)
The brick factory Merkagres de Colombia Ltda., is located in the municipality of El Zulia, department of Norte de Santander, near the city of Cúcuta. It is a company dedicated to the production, sale and commercialization of clay materials for construction, such as bricks, blocks, tablets, etc; and its purpose is the delivery of high quality products for the construction industry and customer satisfaction.